(untitled) (Teaching and Learning Inquiry, 2016)
The goal in this article is to offer a vision for a scholarship of philosophical learning both that philosophers find plausible and helpful and that utilizes our disciplinary skills and knowledge to produce useful insights into how students learn philosophy. Doing so is a challenge because philosophers typically and historically conceive of our work as being properly done in the proverbial armchair, that is, done without being tied to empirical data. To begin, I look at how working from the armchair has typically led to three types of philosophy pedagogy research and I show ways that each can be done well and the limitations of each. Ultimately, I argue that, while useful and revealing in some ways, the techniques typically fail to illuminate where students are in their learning, habits, dispositions and skills. I then briefly explore the use of think alouds, arguing that they offer one viable path to a scholarship of learning in philosophy that allow philosophers to use our own disciplinary skills to make the thinking of our students visible in ways that will help us be clearer about where they are and where we are, so we can better determine how to help them improve. EDITORS’ NOTE This article included embedded videos. To view the videos linked from within the PDF, download the PDF and click the links. If you stay within the preview page, you’ll have to right-click the links and open them in a new window.